AKTIVITAS SOSIAL-BUDAYA SEBAGAI BENTUK INTERAKSI MASYARAKAT MULTIETNIK (STUDI KASUS: KAMPUNG ISLAM KEPAON KOTA DENPASAR) - Agustian, Endy; Rachmawati, Rini; Rijanta, R; Pitoyo, Agus Joko (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2021)
This research is a study related to multiethnic settlements in Indonesia by taking a case study of the Kampung Islam Kepaon in Denpasar City. Kampung Islam Kepaon which is a phenomenon of Muslim settlements in Bali which is filled with cultural acculturation and is the key to harmony with the surrounding Hindu community. The research method used in this research is the case study method by conducting in-depth interviews and observations. After the data is collected, then data analysis is carried out with pattern matching and explanation, and uses a spatial approach in this case spatial pattern analysis and spatial interaction analysis. The results showed that the social and cultural activities in Kampung Islam Kepaon did not only show the relationship between the people in the kampung, but also the relationship between the people who came from outside the Kampung Islam Kepaon. On the other hand, the existence of infrastructure and facilities for the settlement of Kampung Islam Kepaon can make it easier for the local community to carry out socio-cultural activities to interact with the community around the kampung and also as a form to create a sense of tolerance between religious communities.